FAILURE AFTER FUNDOPLICATION: RE-FUNDOPLICATION? IS THERE A ROOM FOR GASTRECTOMY? IN WHICH CLINICAL SCENARIES? - BRAGHETTO,Italo (2019)
ABSTRACT Background: Re-fundoplication is the most often procedure performed after failed fundoplication, but re-failure is even higher. Aim: The objectives are: a) to discuss the results of fundoplication and re-fundoplication in these cases, and b) to analyze in which clinical situation there is a room for gastrectomy after failed fundoplication. Method: This experience includes 104 patients submitted to re-fundoplication after failure of the initial operation, 50 cases of long segment Barrett´s esophagus and 60 patients with morbid obesity, comparing the postoperative outcome in terms of clinical, endoscopic, manometric and 24h pH monitoring results. Results: In patients with failure after initial fundoplication, redo-fundoplication shows the worst clinical results (symptoms, endoscopic esophagitis, manometry and 24 h pH monitoring). In patients with long segment Barrett´s esophagus, better results were observed after fundoplication plus Roux-en-Y distal gastrectomy and in obese patients similar results regarding symptoms, endoscopic esophagitis and 24h pH monitoring were observed after both fundoplication plus distal gastrectomy or laparoscopic resectional gastric bypass, while regarding manometry, normal LES pressure was observed only after fundoplication plus distal gastrectomy. Conclusion: Distal gastrectomy is recommended for patients with failure after initial fundoplication, patients with long segment Barrett´s esophagus and obese patients with gastroesophageal reflux disease and Barrett´s esophagus. Despite its higher morbidity, this procedure represents an important addition to the surgical armamentarium.